RELASI ANTARA KEMAMPUAN PEMECAHAN MASALAH MATEMATIK DAN KEAKTIFAN BELAJAR MATEMATIK SISWA SMP YANG MENGGUNAKAN PENDEKATAN REALISTIC MATHEMATIC EDUCATION BERBANTUAN GEOGEBRA - Citra Megiana Pertiwi; Tiya Fitriani; Muhammad Afrilianto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
The balance between cognitive and mathematical affective abilities is very important to be mastered by students in order to face future challenges. Background of the research is based on the students’ low ability of mathematical problem solving and mathematical learning activeness. The purpose of this research is finding the relation between students’ mathematical problem-solving ability and students’ mathematical learning activeness by using Realistic Mathematics Education approach using GeoGebra. The method in this research is the experimental research in the form of pre-test-post-test Control Group Design. In addition, the population for this research is the entire Public middle schools (SMP Negeri) in West Bandung regency. From all public middle schools in West Bandung, a school named SMP Negeri 3 Batujajar is randomly selected, and two classes of the 1st-gradestudents of the school are selected as the research sampling data. The first class becomes an experimental class which gains learning using GeoGebra assisted realistic mathematics educational approach and the other class gets common learning. The result of the research shows that there is a more positive relationship between mathematical problem-solving ability and mathematical learning activeness of learning by using Realistic Mathematics Education approach with GeoGebra rather than using common learning. In addition, the approach gives positive impacts, such as more interactive learning, understanding concepts, and more meaningful learning.